Strategi Akuisisi Naskah di Perpustakaan Nasional Press dalam Upaya Meningkatkan Bahan Bacaan dan Literasi Masyarakat Indonesia - Damaji Ratmono (Institut Agama Islam Negeri Salatiga, 2022)
This scientific paper discusses the manuscript acquisition strategy carried out by the National Library of Indonesia in an effort to improve reading materials and literacy of the Indonesian people. This writing aims to see the course of the manuscript acquisition strategy carried out by the National Library of Indonesia Press along with the strengths and weaknesses found from this strategy. The method used in this study is a qualitative method. The type or research design used is descriptive research. The data collection techniques were carried out by means of literature review, interviews, and observations. Data analysis techniques were carried out through data reduction, data presentation, and drawing conclusions. The results of literature review, observation, and author interviews at the National Library of Indonesia show that the manuscript acquisition strategy carried out by the National Library of Indonesia Press is that the title of the book has been determined, the author’s request, and collaboration/cooperation. The results also found that the three strategies found their respective advantages and disadvantages. These three strategies can increase the number of publications in the form of books at the National Library of Indonesia Press so that with these efforts it is expected to help the Government improve reading materials and literacy of the Indonesian people.